Changing Patterns of Scaffolding and Autonomy During Individual Music Lessons: A Mixed Methods Approach. Issue 1 (2nd January 2017) - Kupers, Elisa; van Dijk, Marijn; van Geert, Paul
Abstract : Learning implies change. Inside and outside schools, we aim for students to change into people with more skills and knowledge as well as with a growing sense of agency and responsibility. Furthermore, education itself is subject to constant change. In this article, we examine change in 3 case studies in the context of individual music lessons from a complex dynamic systems approach. Three beginning string instrument students and their teacher were followed for 18 months (28 lessons per dyad) by means of video observations. We combine cluster analyses on longitudinal data with qualitative illustrations of moment-to-moment teacher–student transactions to gain insight into how and why change in teaching and learning occurs. The 3 cases show distinct profiles of change: the development of strong suboptimal attractor states, the emergence of optimal attractor states, and a profile that is characterized by falling back into suboptimal attractor states. We discuss how optimal and suboptimal learning and teaching trajectories can unfold over time and how a mixed methods approach can provide valuable new insights for both practice and future research.